2012
DOI: 10.3109/10837450.2012.705299
|View full text |Cite
|
Sign up to set email alerts
|

Application of external lubrication during the roller compaction of adhesive pharmaceutical formulations

Abstract: A novel use of external lubrication has been investigated in which magnesium stearate was applied directly to the roll surface during roller compaction. A scalable parameter; travelling roll distance per shot (D(pS)), has been defined which ensures that an equal amount of magnesium stearate is applied to the roll surface per rotation at any roll speed. It was found that a formulation containing 20% w/w of either the API Pravastatin or Ibipinabant required a smaller D(pS) than a placebo formulation in order to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The region between the base of the hopper and the feed screw has previously been hypothesised to be the most likely area for particle shear to occur within this feed system (Dawes et al, 2013). These findings may also be applicable to different types of feed systems used in other equipment, such as tablet presses and hot-melt extruders.…”
Section: Powder Feed Transmissionmentioning
confidence: 84%
See 1 more Smart Citation
“…The region between the base of the hopper and the feed screw has previously been hypothesised to be the most likely area for particle shear to occur within this feed system (Dawes et al, 2013). These findings may also be applicable to different types of feed systems used in other equipment, such as tablet presses and hot-melt extruders.…”
Section: Powder Feed Transmissionmentioning
confidence: 84%
“…Consequently, the functional relationship between material attributes and unit processes has become an area of great interest. Material characteristics, such as the particle size and shape of the active pharmaceutical ingredient (API), can significantly affect the processing behaviour of drug formulations, including bulk powder properties such as flowability (Carstensen & Chan, 1976), compactibility (Sun & Grant, 2001), bulk density , and propensity for sticking, both in terms of adhesion (Lam & Newton, 1992, Dawes et al, 2013 and cohesion (De Villiers, 1997, Sudah et al, 2002.…”
Section: Introductionmentioning
confidence: 99%
“…They found that zirconia was an alternative to stainless-steel tooling. The addition of exact amount of suitable lubricant directly on to punch and die surfaces immediately after tablet ejection has also been reported by Yamamura et al 7 and Dawes et al 8 . Optimization of lubricant concentration and the choice of alternative lubricants seem an attractive solution of the problem of the deleterious effect of lubricant on the bonding properties of tablet excipients 9 .…”
Section: Introductionmentioning
confidence: 80%
“…Hamdan et al (Hamdan et al, 2010) observed that variations in the roll gap, and hence ribbon density, could be attributed to such adhesion. Dawes et al (Dawes et al, 2012a), concluded that the sticking of an adhesive powder formulation can be inhibited by external lubrication of the rollers using magnesium stearate (MgSt). They also investigated the effects of internal lubrication by incorporating MgSt in the powder feed.…”
Section: Introductionmentioning
confidence: 99%